Developing Entrepreneurial Intention among Retired Indonesian Migrant Workers in Central Java: Key Supporting Determinants - Rodhiyah Rodhiyah; Dede Sri Rahayu; Nadia Ulfa Agustin Hilman; Alfin Nur Fahmi Mufreni; Rani Nurnawati (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
This research aims to analyze the influence of Entrepreneurial Knowledge (EK), Perceived Feasibility (PF), and Entrepreneurial Self-Efficacy (ESE) on Entrepreneurial Intention (EI) among retired Indonesian migrant workers in Central Java. The research employed a quantitative approach by collecting data through questionnaires distributed to 60 respondents. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results indicated that Entrepreneurial Knowledge (EK) had a positive and significant effect on and Perceived Feasibility (PF) also had a positive and significant effect on Entrepreneurial Intention (EI) . In contrast, Entrepreneurial Self-Efficacy (ESE) had no significant effect on Entrepreneurial Intention (EI) . These findings suggest that entrepreneurial intentions among migrant retirees are more strongly influenced by the level of entrepreneurial knowledge and perceptions of business feasibility than by confidence in their own abilities.